PERBANDINGAN DIAMETER DISC TERHADAP JARAK DAN WAKTU PENGEREMAN PADA KENDARAAN YAMAHA MIO - Fadholi, Muhammad; Budiyono, Budiyono; Prasetyo, Imam (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2022)
Currently, there are many aftermarket products that sell various brands of discs of various sizes, which are thought to affect the braking parameters, namely the braking time and distance. One of the things that people often do is modify the size of the disc from a standard size to a larger or smaller size, so that the vehicle can be maximal in braking. Because the braking area is made farther from the center axle of the wheel, the effect is that the brakes can grip the disc more tightly. The purpose of this study was to determine the effect of disc size on distance and braking time and which disc size is better to use. This test was carried out by testing the front brake braking on a flat and straight road on a Yamaha mio using discs measuring 190mm, 200mm, 220mm at each speed of 40km/h, 50km/h, 60km/h by testing 3 times on each disc. discs and speed. The results show that the 220mm disc is the best to use.Keywords: Disc, Distance and Time.